Environmental changes in the north‐east Sunda region over the last 40 000 years - Chuanxiu Luo; Simon Haberle; Zhuo Zheng; Rong Xiang; Chixin Chen; Gang Lin; Kumar Sazal (Journal of Quaternary Science, 2019)
Pollen and spores from 110 samples from sediment core NS07‐25 from the Nansha Trough in the South China Sea (SCS) were analysed with a particular focus on reconstructing vegetation and climate change and identifying the sources of palynomorphs on the Sunda Shelf during the Last Glacial Maximum (LGM). Palynomorph sources were identified using the Near Analysis function in ArcGIS with 62 data points of the pollen in surface sediment samples from the southern SCS. The results showed that during the LGM, pollen and spores came from the exposed Sundaland, whereas before and after the LGM, pollen and spores came from Borneo. Changes in vegetation and climate were inferred from pollen percentages, concentrations and influx and indicated that during the LGM, ferns, lowland rainforests, upper montane rainforests and lower montane forests were present on the north‐east part of the exposed Sunda Shelf but not over the entire Sunda Shelf. Climate during the LGM was cooler than it is today, but humidity was not substantially lower. During the LGM, grasses and shrubs did not cover the southern continental shelf of the SCS, possibly because they were located in the Intertropical Convergence Zone.

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.